2017
DOI: 10.1007/s11695-017-3054-2
|View full text |Cite
|
Sign up to set email alerts
|

Use of Self-Expandable Metal Stents in the Treatment of Leaks Complicating Laparoscopic Sleeve Gastrectomy: A Cohort Study

Abstract: Repeated stenting for leaks after LSG is an effective and safe intervention. The efficacy of partially covered SEMS appears superior to that of the fully covered SEMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…Other severe complications of stent implantation were rare. One reported gastrointestinal perforation [38]. Two studies showed minor bleeding as a complication of stenting [32,34].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Other severe complications of stent implantation were rare. One reported gastrointestinal perforation [38]. Two studies showed minor bleeding as a complication of stenting [32,34].…”
Section: Discussionmentioning
confidence: 99%
“…Leaks were most often located within the gastroesophageal junction (GEJ) near the proximal end of the staple line or in the distal portion of the esophagus, or in the upper third of the gastric stump. The mean [38].…”
Section: Self-expanding Metal and Plastic Stentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have described the efficacy and safety of using partially and fully covered (FC) esophageal self-expandable metallic stents (SEMSs) in the management of post-LSG leakage and stenosis. [ 6 7 8 9 ] However, only a few studies have reported the efficacy of specifically designed FC mega SEMS in the management of post-LSG leakage and stenosis. [ 10 11 12 ] Thus, the present study aimed to assess the efficacy and safety profile of using the mega stent in the management of post-LSG fistulas and stenosis in a single center.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in Saudi Arabia have only reported the use of partially covered SEMS in the management of post-LSG leak. [ 8 ]…”
Section: Introductionmentioning
confidence: 99%